Description of four new HLA alleles in the Finnish population: A*03:283N, A*68:167, C*03:327, C*03:361. (24th October 2017) - Polvi, A.; Peräsaari, J.; Linjama, T.; Saarinen, T.; Koskela, S.; Voorter, C. E. M.; Jaatinen, T.
Abstract : New HLA alleles found in the Finnish population: A*03:283N, A*68:167, C*03:327 and C*03:361 .